Recruitment and Intelligent System - Shatovska, T.; Kamenieva, I. (Інститут проблем штучного інтелекту МОН України та НАН України, 2008)
The Carrier Centre is information, analytical and organizational support of job placements of students and graduates. The information system for supporting all main activities was developed. Nowadays the system strengthens links between students and companies as repository of the CVs and vacancies. On the other side the system should be as a virtual recruiter that take into account student’s personal abilities and preferences, available jobs, Company profiles, local labour market infrastructure, industrial and technological trends, account job specification, available human resource to provide the effective decisions on employment. This paper presents the intelligent management system based on text mining methods for supporting recruitment services.